2018
DOI: 10.1111/nep.13455
|View full text |Cite
|
Sign up to set email alerts
|

Association between albumin and C‐reactive protein and ankle‐brachial index in haemodialysis

Abstract: Aim Peripheral artery occlusive disease (PAOD) is associated with increased rates of cardiovascular mortality, morbidity and hospitalization in patients undergoing dialysis. An ankle‐brachial index (ABI) less than 0.9 has been used to diagnose PAOD. The aim of this study was to evaluate associations among inflammation, malnutrition and their interactions on the risk of PAOD. Methods Two hundred and twenty‐two haemodialysis patients (mean age 61.0 ± 11.7 years, 56.8% men) were enrolled and stratified into four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In the present study, the mean values of both serum protein and albumin were lower in the subjects with peripheral arterial disease. This is comparable to findings in children and adults [ 4 , 55 ]. With proteinuria and resultant hypoproteinaemia there is a compensatory hyperlipidaemia which can lead to endothelial damage and increase the risk of developing peripheral arterial disease.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the mean values of both serum protein and albumin were lower in the subjects with peripheral arterial disease. This is comparable to findings in children and adults [ 4 , 55 ]. With proteinuria and resultant hypoproteinaemia there is a compensatory hyperlipidaemia which can lead to endothelial damage and increase the risk of developing peripheral arterial disease.…”
Section: Discussionsupporting
confidence: 91%
“…The detailed methods of measuring the ABI have been described in previous studies [21,25,26]. ABI was measured once in each patient using an ABI-form device (VP1000; Omron Colin Co. Ltd., Komaki, Japan) and calculated as systolic blood pressure in the ankle/systolic blood pressure in the arm.…”
Section: Assessment Of Ankle-brachial Index (Abi) and Definition Of Paodmentioning
confidence: 99%
“…First, patients with PD have long-term inflammation [ 28 ]. Several studies have revealed that the blood levels of the C-reactive protein and other inflammatory mediators are strongly associated with PAOD [ 29 , 30 ]. Second, oral bacteremia may be a risk factor for PAOD [ 18 ].…”
Section: Discussionmentioning
confidence: 99%